Vivencias y experiencias en las relaciones sociales durante la formación académica de médicos especialistas. - PALACIO-DURÁN, ERIKA; OCHOA-GÓMEZ, FRANQUI; ACOSTA-FERNÁNDEZ, MARTÍN; PINILLOS PATIÑO, YISEL; CONSUEGRA MACHADO, JOSÉ RAFAEL (Salud Uninorte)
Introduction: Academic training in medical specialties is a continuous process of theoretical and practical training where residents constantly interact with program coordinators, residents of different programs and workers in internship scenarios; the relationships that occur in different residences were investigated through interviews. Objective: To know the life experiences of the hierarchy of resident doctors during their training process in the practice settings. Method: Qualitative phenomenological study that uses semi-structured interviews with 42 students of medical-surgical specialties such as: plastic surgery, gynecology, critical medicine, internal medicine, neurology, pediatrics and psychiatry, reviewing the psychosocial risk battery domain of social relations and leadership. Results: The interviewees expressed 195 references related to their experiences where the leadership of the program coordinators is described as a significant interaction generating psychological or protective discomfort, along with 158 references of feedback style in some experiences, scarce or focused on a quantitative note and 156 references of how they saw the relationship with their older residents from a hierarchical perspective. Conclusions: The characteristics of the hierarchy in the residence are determined by the leadership style of the program coordinator and the residents replicate the same model with their peers of the same year, superiors and minor residents.